Factors Analyses of Effecting to Milk Production and Economic Efficiency of Dairy Goat Agribisness In Kaligesing District of Purworejo Region - Astuti, Triana Yuni; Haryati, Sri; Siswadi, Siswadi (ANIMAL PRODUCTION, 2002)
A survey in the agribusiness of dairy goat smallholder had been conducted in Kaligesing district of Purworejo region at 13 rd September up to 7th November 2001. The survey studied the factors effecting the milk yield, in how the factors influence economically. Forty eight respondents (dairy goat smallholders) were used in this study and interview method was applied for collecting data. The variables were observed; lactation goat, man power, garage, and concentrate ration. Cobb-Douglass method was applied for analyzing the data. To know the economic efficiency of the agribusiness was approached by the ratio between the Marginal Product Value an input cost. From the data analysis it could be in formatted that the numbers of lactating goat and the numbers of lactating goat and the numbers of concentrate were significant influence on the milk yield, white the man power and the forage were not significant influence. For the numbers of lactating goat and concentrate, economically the efficiency was not yet reached, so the use of the factors were ought to be increased up to an appoint limited. On the other hand the man power and forage was not efficient, so the use of the factors need to be descreased. (Animal Production 4(1): 27-31 (2002)Key word : Production factors, economics efficiency, dairy goat PE